Pemahaman Peraturan Perpajakan, Tarif Pajak dan Kesadaran Wajib Pajak pada Pelaku Bisnis Online Shop di Kota Tebing Tinggi - Pradila, Egita; Nurlaila; Nasution, Juliana (Jurnal Pustaka Cendekia Pendidikan, 2023)
People who have minimal insight or knowledge result in a lack of knowledge in carrying out tax obligations and ending with non-compliance to carry out these obligations in making tax payments. This study aims to determine the understanding of taxpayers, tax rates and awareness of taxpayers in online shop businesses. This research method applies a qualitative descriptive method in displaying knowledge about taxation, tax rates and taxpayer awareness among online shop business people in Tebing Tinggi City. Based on the results of the first study, Taxpayers' Understanding of Government Regulation Number 23 of 2018 Concerning MSME Tax (Case Study of Taxpayers Registered at the Tebing Tinggi Pratama Tax Office) states that taxpayers' understanding of Government Regulation Number 23 of 2018 is still minimal. Second, Knowledge of all obligations regarding government policy No. 23 of 23 which emphasizes seeing tariffs but without knowing the contents of the provisions regulated to identify PP No. 23 of 2018 Taxpayers are only limited to knowing and there are changes to regulations regarding MSME tariffs. Third, the awareness of onlineshop actors is very minimal about taxes, so there is a great need for accurate and thorough re-socialization regarding the application of income tax so that onlineshop business operators can comply with and understand applicable regulations.